Effect of Anti-S100A4 Monoclonal Antibody Treatment on Experimental Skin Fibrosis and Systemic Sclerosis-Specific Transcriptional Signatures in Human Skin - Trinh-Minh, Thuong; Györfi, Andrea-Hermina; Tomcik, Michal; Tran-Manh, Cuong; Zhou, Xiang; Dickel, Nicholas; Tümerdem, Bilgesu Safak; Kreuter, Alexander; Burmann, Sven-Niklas; Borchert, Signe Vedel; Hussain, Rizwan Iqbal; Hallén, Jonas; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2024)
OBJECTIVE: S100A4 is a DAMP protein. S100A4 is overexpressed in patients with systemic sclerosis (SSc), and levels correlate with organ involvement and disease activity. S100A4-/- mice are protected from fibrosis. The aim of this study was to assess the antifibrotic effects of anti-S100A4 monoclonal antibody (mAb) in murine models of SSc and in precision cut skin slices of patients with SSc. METHODS: The effects of anti-S100A4 mAbs were evaluated in a bleomycin-induced skin fibrosis model and in Tsk-1 mice with a therapeutic dosing regimen. In addition, the effects of anti-S100A4 mAbs on precision cut SSc skin slices were analyzed by RNA sequencing. RESULTS: Inhibition of S100A4 was effective in the treatment of pre-established bleomycin-induced skin fibrosis and in regression of pre-established fibrosis with reduced dermal thickening, myofibroblast counts, and collagen accumulation. Transcriptional profiling demonstrated targeting of multiple profibrotic and proinflammatory processes relevant to the pathogenesis of SSc on targeted S100A4 inhibition in a bleomycin-induced skin fibrosis model. Moreover, targeted S100A4 inhibition also modulated inflammation- and fibrosis-relevant gene sets in precision cut SSc skin slices in an ex vivo trial approach. Selected downstream targets of S100A4, such as AMP-activated protein kinase, calsequestrin-1, and phosphorylated STAT3, were validated on the protein level, and STAT3 inhibition was shown to prevent the profibrotic effects of S100A4 on fibroblasts in human skin. CONCLUSION: Inhibition of S100A4 confers dual targeting of inflammatory and fibrotic pathways in complementary mouse models of fibrosis and in SSc skin. These effects support the further development of anti-S100A4 mAbs as disease-modifying targeted therapies for SSc.
Keywords: Animals; Female; systémová sklerodermie; S100 Calcium-Binding Protein A4; ženské pohlaví; Fibrosis; STAT3 Transcription Factor; Antibodies, Monoclonal; lidé; Mice; kůže; Scleroderma, Systemic; myši; Bleomycin; transkripční faktor STAT3; modely nemocí na zvířatech; Skin; S100 kalcium vázající protein A4; Disease Models, Animal; monoklonální protilátky; zvířata; fibróza; bleomycin; Humans